2017
DOI: 10.4187/respcare.05260
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cough Peak Flow Measured by a Ventilator to Predict Re-Intubation When a Spirometer Is Unavailable

Abstract: CPF measurement by a ventilator was convenient, affordable, and safe. It had a predictive accuracy for re-intubation similar to that of a spirometer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 23 publications
1
30
0
1
Order By: Relevance
“…As a predictor of extubation failure, PCED appears to be as accurate as CPF after a successful SBT. These results are consistent with those of previous studies, which reported that low CPF was significantly associated with extubation failure and that PCED was significantly correlated with CPF in healthy adults [8,9,[17][18][19][20][21]. This is the first study to investigate associations of ultrasonographic indices of diaphragm movement during cough with simultaneously measured CPF and extubation outcome in mechanically ventilated patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As a predictor of extubation failure, PCED appears to be as accurate as CPF after a successful SBT. These results are consistent with those of previous studies, which reported that low CPF was significantly associated with extubation failure and that PCED was significantly correlated with CPF in healthy adults [8,9,[17][18][19][20][21]. This is the first study to investigate associations of ultrasonographic indices of diaphragm movement during cough with simultaneously measured CPF and extubation outcome in mechanically ventilated patients.…”
Section: Discussionsupporting
confidence: 92%
“…Peak velocity of the diaphragm was measured by placing the tissue Doppler imaging cursor at the posterior one-third of the right hemidiaphragm ( Figure 2) [15]. Simultaneous measurement of CPF was performed for both coughs by using the internal flow meter of the ventilator (PB840, Covidien, Mansfield, MA, USA) [17].…”
Section: Observations and Measurementsmentioning
confidence: 99%
“…In the previous studies, CPF was measured with various devices, such as flow meters, spirometers and pneumotachographs. However, not all medical facilities provide these devices [14]. Moreover, the complex device setup, including firmly attaching the facemasks and infection control filters on the patient [1], imposes burdens on both patients and their caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…Various spirometers [3,[23][24][25][26] and peak flow meters [24,[26][27][28][29][30] are used for CPF measurement. Moreover, various flow sensors, such as a pneumotachograph [21,[23][24][25]31] that measures respiratory flow using differential pressure sensors, a constant temperature hot-wire flow sensor ( Figure 2a) [26,32] and an ultrasonic sensor [33], are used in spirometers. In particular, the peak flow meter that can measure the flow rate using a spring-loaded piston is most commonly used because of its small size and ease of use, enabling patients to measure CPF by themselves ( Figure 2b).…”
Section: Cough Mechanism and Related Factors Influencing Cpfmentioning
confidence: 99%
“…CPF was measured using various devices (Figure 2). However, some medical facilities do not provide these devices [25], and some studies have used a semiquantitative cough strength assessment method [47,48]. Moreover, the complex setup of the device, including firm attachment of the facemask and infection control filter to the patient, imposes a burden on both patients and caregivers.…”
Section: Cpf Estimation Model Using Cough Soundsmentioning
confidence: 99%